Geng Motor di Indonesia Perspektif Fenomenologi - Jauhar Jauhar (Madani Jurnal Politik dan Sosial Kemasyarakatan, 2018)
This study shows that juvenile delinquency in a "container" called motorcycle gang makes people uncomfortable with acts of violence carried out individually (alone) or groups. They feel proud if people are afraid, there is a sense of pride in motorcycle gang members who are able to knock down opponents, damage other people's property, rob, and damage public facilities. This is a disaster for the community. The method used is a qualitative method with descriptive studies. The data collection technique is documentation and literature review. The results showed that there was a role for communication by parents to teenage motorcycle gang.